1998
DOI: 10.1002/(sici)1097-0142(19980901)83:5<858::aid-cncr9>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Micrometastasis and tumor cell microinvolvement of lymph nodes from esophageal squamous cell carcinoma

Abstract: BACKGROUND The purpose of this study was to investigate micrometastasis (MM) and tumor cell microinvolvement (TCM) in the regional lymph nodes of patients with esophageal squamous cell carcinoma (SCC). METHODS MM was defined as individual tumor cells or tumor cell clusters <0.5 mm in greatest dimension with a surrounding stromal reaction. TCM was defined as individual tumor cells or tumor cell clusters without a surrounding stromal reaction. One thousand nine hundred and fifty‐four lymph nodes were dissected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…rates by RT-PCR assay than conventional histopathological examination (Bilchik et al, 2001;Kitagawa & Kitajima, 2002;Maruyama et al, 1999;Natsugoe, et al, 1998;Noura et al, 2002), these results showed high sensitivity and specificity of the ATX-S10Na (II)-guided method for the detection of SNs. Because micrometastasis occurs frequently in gastric carcinoma, the system using ATXS10Na (II) may be a novel technology to detect micrometastases with high sensitivity, resulting in reduction of false-negative LNs.…”
Section: Novel Biomedical Imaging Approach For Detection Of Sentinel mentioning
confidence: 69%
“…rates by RT-PCR assay than conventional histopathological examination (Bilchik et al, 2001;Kitagawa & Kitajima, 2002;Maruyama et al, 1999;Natsugoe, et al, 1998;Noura et al, 2002), these results showed high sensitivity and specificity of the ATX-S10Na (II)-guided method for the detection of SNs. Because micrometastasis occurs frequently in gastric carcinoma, the system using ATXS10Na (II) may be a novel technology to detect micrometastases with high sensitivity, resulting in reduction of false-negative LNs.…”
Section: Novel Biomedical Imaging Approach For Detection Of Sentinel mentioning
confidence: 69%
“…Glickman et al 21 did not ®nd a correlation between the presence of occult lymph node metastasis and poor survival for patients with oesophageal cancer. In contrast, Izbicki et al 8 and Natsugoe et al 9 have found nodal micrometastases to be a signi®cant indicator of a poorer prognosis after oesophagectomy. The authors' previous study was consistent with the ®ndings of the latter authors 7 .…”
Section: Discussionmentioning
confidence: 92%
“…Natsugoe et al 9 have demonstrated that patients without overt nodal metastasis but with newly identi®ed micrometastases have the same poor prognosis as patients with overt metastasis. The same in¯uence of nodal micrometastasis on postoperative survival was observed in the present study; the survival curve of patients without overt metastasis but with micrometastases was similar to that of patients with one to four overt metastatic nodes not accompanied by micrometastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in patients with advanced cancer, distant lymph nodes should be removed if LNM is found in regional lymph nodes. In patients with carcinoma of the oesophagus and stomach, the reported prognosis was worse in those with LNM (35,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%